2011
DOI: 10.1002/anie.201008286
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Nanoshelled Microcapsules: A Theranostic Agent for Ultrasound Contrast Imaging and Photothermal Therapy

Abstract: A valuable shell: The combination of electrostatic deposition of gold nanoparticles onto microcapsules and a surface seeding method results in the formation of gold nanoshells (see picture). This nano/microcomposite is able to operate as a theranostic agent for both contrast‐enhanced ultrasonic imaging (diagnostic) and photohyperthermia (therapeutic), and thus holds a great potential for photothermal therapy in cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
242
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(247 citation statements)
references
References 16 publications
0
242
1
1
Order By: Relevance
“…At the concentration of 0.25 mg mL À1 ,t he solutions could be easily heatedu pt oa bove 42 8C, this temperature helps to kill cancerc ells. [28] These data revealed that the temperature deliveredb yt he PPY@PAA/fmSiO 2 NPs could be effectively regulated;t his material has great potentialf or thermal ablation of malignant tissues. To furtheri nvestigate the photothermal transduction efficiency of the PPY@PAA/fmSiO 2 aqueous solution,w er ecorded the temperature change of the sample solution with the concentrationo f0 .3 mg mL À1 as afunction of time under the 808 nm laser at the power density of 2.0 Wcm À2 continuous irradiation for 300 s( Figure 3B and 3C).…”
Section: Resultsmentioning
confidence: 97%
“…At the concentration of 0.25 mg mL À1 ,t he solutions could be easily heatedu pt oa bove 42 8C, this temperature helps to kill cancerc ells. [28] These data revealed that the temperature deliveredb yt he PPY@PAA/fmSiO 2 NPs could be effectively regulated;t his material has great potentialf or thermal ablation of malignant tissues. To furtheri nvestigate the photothermal transduction efficiency of the PPY@PAA/fmSiO 2 aqueous solution,w er ecorded the temperature change of the sample solution with the concentrationo f0 .3 mg mL À1 as afunction of time under the 808 nm laser at the power density of 2.0 Wcm À2 continuous irradiation for 300 s( Figure 3B and 3C).…”
Section: Resultsmentioning
confidence: 97%
“…Polymeric micelles combined with lipid shelled bubbles have also been developed as ultrasound-sensitive theranostic nanocarriers for siRNA for tumor gene therapy 87 . In another approach, gold nanoparticles and gold shell nanocapsules were utilized as theranostic agents for image-guided photothermal therapy for cancer 88-91 . In this case, the perfluorooctylbromide (PFOB) was incorporated as the contrast agent, which enhanced ultrasound echogenicity for diagnostic purposes and located the disease site for enhanced tumor ablation.…”
Section: Therapeutic Applications Of Nano-scale Ultrasound Contrast Amentioning
confidence: 99%
“…These stable and biocompatible MSNs are localized and bind to the targeted site and release the payload drugs. Furthermore, the UCAs were able to couple to paramagnetic compounds, such as superparamagnetic iron oxide nanoparticle (SPIOs), to produce bi-functional agents that have both ultrasound and MRI imaging capability for tumor treatments 88, 89, 96, 97 . The bimodal imaging platform provides excellent diagnosis information and precise location for the therapeutic focusing spot for photothermal therapy.…”
Section: Therapeutic Applications Of Nano-scale Ultrasound Contrast Amentioning
confidence: 99%
“…113 Ke et al have used gold-nanoshelled microcapsules (GNS-MCs) for PTT and ultrasound contrast imaging, in which the temperature was more than 42 °C with 0.3-0.5 mg/mL GNS-MCs (808 nm at 2-8 W/cm 2 for 10 minutes with a CW fibercoupled diode laser) for sufficient cell killing. 114 Yang et al reported NIR photothermal ablation of cancer cells using polyaniline NPs that NIR irradiation allowed high temperature rise (54.8 °C at 808 nm and 2.45 W/cm 2 for 5 minutes) which is compared to that for pure water (6.6 °C). 115 Hirsh and coworkers developed GNSs and evaluated them against human breast carcinoma cells for photothermally-induced cell death by NIR (820 nm at 35 W/cm 2 ).…”
Section: Ptt and Gnpsmentioning
confidence: 98%
“…GNPs are widely used NPs based on their chemical inertness, minimum toxicity, large surface-to-volume ratios and easy tuning of the NPs size that has potential applications, especially, in drug delivery (PDT drugs, insulin, tocopherol, and other drugs), 101-106 cancer diagnosis, [107][108][109] and PTT. [107][108][109][110][111][112][113][114][115] Cheng et al developed GNPs incorporating the silicon phthalocyanine derivative as the PS delivery platform which revealed efficient in vivo release and penetration of the PS into the cancer. 70,71 GNPs could be protected from opsonization and subsequent clearance by macrophages resulting in extended circulation time in the blood, followed by preferential accumulation in tumor sites, the so-called "enhanced permeability and retention" effect.…”
Section: B Il Type Pss and Gold Nanoparticles (Gnps)mentioning
confidence: 99%